2015
DOI: 10.1371/journal.pone.0134830
|View full text |Cite
|
Sign up to set email alerts
|

Time-Point Dependent Activation of Autophagy and the UPS in SOD1G93A Mice Skeletal Muscle

Abstract: Amyotrophic Lateral Sclerosis (ALS) is a fatal neurodegenerative disease characterized by a selective loss of motor neurons together with a progressive muscle weakness. Albeit the pathophysiological mechanisms of the disease remain unknown, growing evidence suggests that skeletal muscle can be a target of ALS toxicity. In particular, the two main intracellular degradation mechanisms, autophagy and the ubiquitin-proteasome degradative system (UPS) have been poorly studied in this tissue. In this study we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…Second possibility is that SQSTM1 expressing in cells and tissues other than neurons affects the onset of disease in SOD1 H46R mice. Evidences showing that, in skeletal muscle of a SOD1 G93A -expressing ALS mouse model, the UPS is activated prior to the onset of disease, while the autophagic degradation pathway is activated after the onset of disease till at end-stage [ 36 ], suggest a possible pathogenic interaction between proteostasis in skeletal muscles and neurodegeneration. Since the expression level of transgene-coded SQSTM1 in skeletal muscle is higher than those in other tissues (Additional file 1 : Figure S1b), it is possible that the earlier onset of disease in SQSTM1 ; SOD1 H46R mice is linked to dysregulation of autophagy by SQSTM1 overexpression in skeletal muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Second possibility is that SQSTM1 expressing in cells and tissues other than neurons affects the onset of disease in SOD1 H46R mice. Evidences showing that, in skeletal muscle of a SOD1 G93A -expressing ALS mouse model, the UPS is activated prior to the onset of disease, while the autophagic degradation pathway is activated after the onset of disease till at end-stage [ 36 ], suggest a possible pathogenic interaction between proteostasis in skeletal muscles and neurodegeneration. Since the expression level of transgene-coded SQSTM1 in skeletal muscle is higher than those in other tissues (Additional file 1 : Figure S1b), it is possible that the earlier onset of disease in SQSTM1 ; SOD1 H46R mice is linked to dysregulation of autophagy by SQSTM1 overexpression in skeletal muscles.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found LC3-II and LAMP-1 were significantly decreased in the cone region of KC epithelium from Grades II and III compared to the peripheral region. This could be due to insufficient autophagy activity in the diseased area (cone) compared to the matched peripheral region during disease progression or an altered expression of autophagic markers, which has been observed in other disease conditions [ 28 , 29 ]. A difference in the expression levels (low, medium, high) of autophagosomal marker LC3 has been shown in KC epithelium, but without clinical disease classification, thereby demonstrating alterations in the autophagic pathway [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it was shown that skeletal muscle‐restricted expression of mutant human SOD1 (hSOD1) causes motor neuron degeneration in an ALS mouse model , and recent findings suggest that skeletal muscle may actively participate in ALS pathogenesis. Indeed, gene expression changes, increased oxidative stress, impaired protein degradation, defective mitochondrial dynamics and disturbed calcium homeostasis in the skeletal muscle from ALS animal models and human ALS patients were detected early in disease progression . Furthermore, activation of inflammatory pathways in the context of tissue remodelling have been described in skeletal muscle of SOD1 (G93A) rats and in human sALS patients .…”
Section: Introductionmentioning
confidence: 99%